Sumudu Transform Method for Analytical Solutions of Fractional Type Ordinary Differential Equations - Demiray, Seyma Tuluce; Bulut, Hasan; Belgacem, Fethi Bin Muhammad (Hindawi Ltd, 2015)
We make use of the so-called Sumudu transform method (STM), a type of ordinary differential equations with both integer and noninteger order derivative. Firstly, we give the properties of STM, and then we directly apply it to fractional type ordinary differential equations, both homogeneous and inhomogeneous ones. We obtain exact solutions of fractional type ordinary differential equations, both homogeneous and inhomogeneous, by using STM. We present some numerical simulations of the obtained solutions and exhibit two-dimensional graphics by means of Mathematica tools. The method used here is highly efficient, powerful, and confidential tool in terms of finding exact solutions.